Model Hipotetik: Pendekatan Solution-Focused Brief Counseling (SFBC) dalam Keluarga - Suciani Latif; Musfirah Musfirah (Universitas Mathla'ul Anwar Banten, 2019)
HYPOTHETIC MODEL: AN APPROACH OF SOLUTION-FOCUSED BRIEF COUNSELING (SFBC) IN THE FAMILY. This study is aimed to study hypothetically about Solution-Focused Brief Counseling (SFBC) application in family and some example cases of family counseling that focused on solution. The SFBC is a post-modern counseling approach that is developed in 1982 by Insoo Kim Berg and De Shazer. SFBC is an approach based on counselee strength and potency, and focused to the solution and future. In solving the problem, SFBC families more focus on nowadays problems and immediately move to build solution to repair family situation. Counselee strength is a primary asset to build solution of the problem.